Variable Secondary Metabolite Profiles Across Cultivars of Curcuma longa L. and C. aromatica Salisb. - Kulyal, Poonam; Acharya, Satyabrata; Ankari, Aditya B.; Kokkiripati, Praveen K.; Tetali, Sarada D.; Raghavendra, Agepati S. (Frontiers in Pharmacology, 2021)
Abstract Background: Curcuma spp. (Zingiberaceae), are used as a spice and coloring agent. Their rhizomes and essential oils are known for medicinal properties, besides their use in the flavoring and cosmetic industry. Most of these biological activities were attributed to volatile and non-volatile secondary metabolites present in the rhizomes of Curcuma spp. The metabolite variations among the species and even cultivars need to be established for optimized use of Curcuma spp. Objectives: We compared the phytochemical profiles of rhizomes and their essential oils to establish the variability among seven cultivars: five of Curcuma longa L. (Alleppey Supreme, Duggirala Red, Prathibha, Salem, Suguna), and two of C. aromatica Salisb. (Kasturi Araku, Kasturi Avidi). The GC-MS and LC-MS-based analyses were employed to profile secondary metabolites of these selected cultivars. Methods: Rhizomes of Curcuma spp. were subjected to hydro-distillation to collect essential oil and analyzed by GC-MS. The methanol extracts of fresh rhizomes were subjected to LC-MS analyses. The compounds were identified by using the relevant MS library databases as many compounds as possible. Results: The essential oil content of the cultivars was in the range of 0.74% to 1.62%. Several compounds were detected from the essential oils and rhizome extracts by GC-MS and LC-MS, respectively. Of these, 28 compounds (13 from GCMS and 15 from LCMS) were common in all seven cultivars, e.g. α-Thujene, and diarylheptanoids like Curcumin. Further, a total of 39 new compounds were identified from C. longa L. and/or C. aromatica Salisb., most of them being cultivar-specific. Of these compounds, 35 were detected by GC-MS analyses of essential oils: 1,2-Cyclohexanediol, 1-methyl-4-(1-methylethyl)-; santolina alcohol; to name a few. The other four compounds were detected by LC-MS of the methanolic extracts of the rhizomes, e.g., kaempferol-3,7-O-dimethyl ether and 5,7,8-trihydroxy-2′,5′-dimethoxy-3′,4′-methylene dioxyisoflavanone. Conclusions: We identified and recorded the variability in the metabolite profiles of essential oils and whole rhizome extracts from seven cultivars of Curcuma longa L. and C. aromatica Salisb. As many as 39 new metabolites were detected in these seven Indian cultivars of Curcuma spp. Many of these compounds have health benefits.